The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.apr.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric consequences of trade and human development: A case of BRIC countries

Abstract: Trade Human development indicator BRIC GMM a b s t r a c tThis paper looks into the causal association between economic growth, CO 2 emission, trade volume, and human development indicator for Brazil, Russia, India, and China (BRIC countries) during 1980e2013. Following a generalized method of moments (GMM) technique, we have found out that bidirectional causality exists between CO 2 emissions and economic growth. Feedback hypothesis is supported between CO 2 emissions and human development, trade volume and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
36
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 75 publications
10
36
0
2
Order By: Relevance
“…The coefficient of trade openness for all four cases is positive and significant, which implies that trade openness has a positive impact on economic growth in N-11 economies. This result aligns with the results for Turkey (Ozturk and Acaravci, 2013), newly industrialized countries (Hossain, 2011), BRICS countries (Sinha and Sen, 2016), and several other contexts.…”
Section: Empirical Results and Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The coefficient of trade openness for all four cases is positive and significant, which implies that trade openness has a positive impact on economic growth in N-11 economies. This result aligns with the results for Turkey (Ozturk and Acaravci, 2013), newly industrialized countries (Hossain, 2011), BRICS countries (Sinha and Sen, 2016), and several other contexts.…”
Section: Empirical Results and Discussionsupporting
confidence: 78%
“…The negative impact of CO 2 emissions on economic growth bears this evidence. This aspect has been supported by numerous prior studies (e.g., Sebri and Ben-Salha, 2014;Zeb et al, 2014;Shahbaz et al, 2015;Kang et al, 2016;Sinha and Sen, 2016;Wang et al, 2016, and many others). Conversely, the technical effect that is exerted by trade openness impacts economic growth positively and significantly.…”
Section: Empirical Results and Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This suggests that as the income is increased, the income inequality initially is increased as well up to a certain point and thereafter pollution starts to decline. The majority of the studies exploited panel data based on country level and they found that the EKC hypothesis holds Krueger, 1991, 1995;Panayotou, 1997;Selden and Song, 2004;Vollebergh et al, 2009;Giovanis, 2013;Bölük and Mert, 2014;Giovanis and Ozdamar, 2016;Sinha, 2006;Sinha and Sudipta, 2016Sinha and Bhattacharya, 2016, 2017. Thus, the correlation standalone is not enough to reveal the relationship between income and pollution, where a quadratic relationship between air pollution and income may be present.…”
Section: Summary Statisticsmentioning
confidence: 99%
“…The study uses two dummy variables such as religion and culture to identify their effects on gender inequality as Cooray and Potrafke (2011) found that both culture and religion have a substantial impact on gender inequality. This study also controls average health expenditure to identify their effect on reducing gender inequality in health and survival (Sinha and Sen, 2016). 4…”
Section: Rationale Of the Control Variablesmentioning
confidence: 99%